The Potential of CRISPR/Cas9 to Generate SPAG5 Knockout Breast Cancer Cell Lines - Duffy, Emma (Auckland University of Technology, 2023)
Breast cancer is one of the leading causes of death in women worldwide. In Aotearoa alone, more than 600 wāhine will lose their lives to breast cancer annually, despite receiving professional treatment. Breast cancer is primarily treated with chemotherapy, often in conjunction with radiation and/or surgery. While these treatments are often effective, recurrence rates remain significant, and the adverse effects experienced while undergoing treatment hugely impact patient quality of life. This is in large part due to the non-specific nature of the currently available chemotherapy drugs. Chemotherapy drugs target cancer cells efficiently, however healthy proliferating cells are also impacted. As breast cancer is a heterogeneous disease, multiple targeted treatments are necessary to address the need for increased specificity and efficacy of available treatments. It is essential that novel targets are identified to function as biomarkers and therapeutic targets that do not adversely affect healthy cells in patients with breast cancer. SPAG5 is a novel biomarker for predicting patients’ chemotherapy drug response. SPAG5 is a mitotic-associated protein responsible for regulating and stabilising chromatid segregation and is often upregulated in cancer. Furthermore, SPAG5 interactions with essential cancer-associated mitotic proteins such as p53 suggest SPAG5 is a promising potential therapeutic target. The aim of this project is to determine whether novel CRISPR/Cas9 technology may be utilised to produce SPAG5 knockout clones in cancer cell lines. By producing such cell lines, the hope is to provide further opportunities for the development of novel therapeutics in the treatment of breast and other cancers by targeting SPAG5. Triple-negative breast carcinomas have high mitotic activity, poor spindle formation and high levels of unregulated proliferative growth, all characteristics that have been linked to SPAG5 function. CRISPR/Cas9 is rapidly becoming the most prominently utilised approach for editing cell lines. The rapid and specific nature of the technology provides an accurate and efficient approach to gene editing not previously possible. In this project, CRISPR/Cas9 technology will be utilised to create SPAG5 knockout triple-negative breast cancer cell lines MCF-7 and BT549. To determine the successful generation of SPAG5 knockout BT549 and MCF-7 cell lines, the goal of this thesis was to perform PCR, western blotting and DNA sequencing and analyse the results. Due to COVID-19 lockdowns, and extended COVID-related illness, all these confirmation techniques were performed except a second Western Blotting to confirm the disruption of SPAG5. Nonetheless, the results indicate two SPAG5-knockout cell lines were achieved within triple-negative breast cancer cell lines. The development of such lines provides opportunities for further research to determine more targeted breast cancer treatments, utilising SPAG5 as both a therapeutic target and as a biomarker for individualised treatments.